Penambahan dan Pengurangan dalam Penerjemahan - Fudyartanto, Fuad Arif (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
In doing his work, a translator cannot always present all the meanings contained in the source text comprehensively. He sometimes should reduce the existing meaning, or add a new meaning in the target text, which then results in the phenomenon of “gain” and “loss” of translation. A factor causing this is the fact that no languages have an absolute likeness. Another factor is the cultural gaps in which the languages involved exist. This strategy is commonly taken up by the translator to give an explanation and reason, and to put an emphasis, which are all ultimately aimed to keep the naturality of translation, without sacrificing the loyality of the original content